2020
DOI: 10.1111/jth.14730
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the ubiquitin‐proteasome system in platelets

Abstract: Platelets are small anucleate blood cells with a life span of 7 to 10 days. They are main regulators of hemostasis. Balanced platelet activity is crucial to prevent bleeding or occlusive thrombus formation. Growing evidence supports that platelets also participate in immune reactions, and interaction between platelets and leukocytes contributes to both thrombosis and inflammation. The ubiquitin‐proteasome system (UPS) plays a key role in maintaining cellular protein homeostasis by its ability to degrade non‐fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 85 publications
0
30
0
Order By: Relevance
“…Platelets interact with B‐cells through CD40L‐CD40 participating in Ab isotype switch, and with T cells increasing the frequency of IFN‐γ‐expressing Th1 subset 149 . Importantly, platelets have the necessary machinery for Ag presentation, including immunoproteasome, β2‐microglobulin, and all human leukocyte Ags (HLA) (or MHC in mice) class I subunits 151–153 . Platelets also express the co‐stimulatory molecules CD86, CD40, and ICOSL, being able to present Ags to T lymphocytes inducing both IL‐2 and IFN‐γ secretion and CD69 and IL‐2R expression 154 …”
Section: Innate Immune Receptors In Platelet‐leukocyte Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets interact with B‐cells through CD40L‐CD40 participating in Ab isotype switch, and with T cells increasing the frequency of IFN‐γ‐expressing Th1 subset 149 . Importantly, platelets have the necessary machinery for Ag presentation, including immunoproteasome, β2‐microglobulin, and all human leukocyte Ags (HLA) (or MHC in mice) class I subunits 151–153 . Platelets also express the co‐stimulatory molecules CD86, CD40, and ICOSL, being able to present Ags to T lymphocytes inducing both IL‐2 and IFN‐γ secretion and CD69 and IL‐2R expression 154 …”
Section: Innate Immune Receptors In Platelet‐leukocyte Interactionsmentioning
confidence: 99%
“…149 Importantly, platelets have the necessary machinery for Ag presentation, including immunoproteasome, 2-microglobulin, and all human leukocyte Ags (HLA) (or MHC in mice) class I subunits. [151][152][153] Platelets also express the costimulatory molecules CD86, CD40, and ICOSL, being able to present Ags to T lymphocytes inducing both IL-2 and IFN-secretion and CD69…”
Section: Innate Immune Receptors In Platelet-leukocyte Interactionsmentioning
confidence: 99%
“…Lately, it was shown that platelets acquired all machinery for antigen-presenting through megakaryocytes [ 63 ]. Even though megakaryocytes are found to express both MHC class I and II molecules, the platelets proteome and experimental evidence show only active MHC class I presentation [ 59 , 63 , 64 ]. Interestingly, the declined level of MHC class I molecules on the surface could indicate platelet aging [ 65 ].…”
Section: Platelets Biology and Functionsmentioning
confidence: 99%
“…An additional layer in platelet regulation is the ubiquitin-proteasome system, which maintains cellular protein homeostasis, regulates signal transduction cascades, and supplies MHC class I molecules with peptides for antigen presentation [ 64 ]. Platelets express standard and immunoproteasome subunits and display three protease activities, caspase-like, trypsin-like, and chymotrypsin-like activity, executed by the catalytically active β subunits [ 64 , 160 ]. To undergo proteasome degradation, proteins first need to be marked by ubiquitination, a PTM where a small, highly conserved protein called ubiquitin (Ub) is covalently bonded to a lysine residue.…”
Section: Platelets Proteomicsmentioning
confidence: 99%
“…Platelets are estimated to harbor approximately 80,000 MHC-I molecules on their surface [ 92 ], however, there are controversies regarding the functionality and origin of these molecules on platelets [ 93 ]. Nonetheless, it is now known that platelets (and MK) contain all the molecules necessary for antigen processing and presentation to CD8+ T-cells including a complete proteasome [ 149 , 150 ] and co-stimulatory molecules [ 151 , 152 ]. Although the platelet’s surface contains mainly denatured MHC-I molecules, intracellularly, platelets have a large pool of fully intact functional MHC-I molecules that are expressed upon activation.…”
Section: Introductionmentioning
confidence: 99%